ANALYSIS OF CREDIT DISBURSEMENT OF NATIONAL PRIVATE BANKS IN 2011-2021 PERIOD (CASE STUDY OF NATIONAL PRIVATE BANKS WITH UNHEALTHY LIQUIDITY) - Putu Devi Agustina Prayoga; Hascaryani, Tyas Danarti (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
Bank is an institution with an intermediary function as collecting public funds and channeling them in the form of credit. According to its function in extending credit, bank liquidity conditions are very important in order to minimize the risk of default and other systemic risks. Private banks, which are the most common type of bank in Indonesia, have several banks with unhealthy levels of liquidity because they exceed Bank Indonesia's liquidity provisions. This research was conducted to find out how the influence of sources of funds, profitability, credit risk, monetary and macroeconomic policies affect private bank lending with unhealthy liquidity. This study consists of 8 samples which will be processed using panel data regression on E-Views with data sourced from secondary sources. The results show that sources of funds and credit risk have a significant effect on lending and profitability, monetary policies and macroeconomic have no effect on it.